PENGARUH EDUKASI MENGGUNAKAN LEAFLET TERHADAP TINGKAT PENGETAHUAN IBU HAMIL TERKAIT ASI EKSKLUSIF DI WILAYAH PUSKESMAS TERAJU - Zulfitri, Zulfitri; Hakim, Riska Ismawati; Monalisa, Dian (Fakultas Ilmu Kesehatan, 2024)
Exclusive breastfeeding in the world according to WHO (2020) reached 66%. The national exclusive breastfeeding achievement in the country in 2023 is still less than the target achievement of 80%. The low achievement of the exclusive breastfeeding program occurs due to several factors, including the low knowledge of mothers about exclusive breastfeeding. To improve knowledge about exclusive breastfeeding, it is necessary to provide education and health education to breastfeeding mothers. This study was conducted to determine whether providing education using leaflets affects the level of knowledge of pregnant women related to exclusive breastfeeding in the Teraju Health Center area in 2024. This study used a pre-experiment method of one-group pretest-post-test design, while the sampling technique used was non-probability and obtained 69 samples. Data analysis was carried out with the T-test test at a significance level of 0.05. The results showed that most respondents were aged 20-30 years (72.50%) and had a high school education (40.60%). Before the provision of education, the average value of the level of knowledge of pregnant women was 68.26 and after the provision of education, the average level of knowledge of pregnant women became 85.00. The t-test showed a p-value of 0.00 which means provision of education with leaflets affects the knowledge of pregnant women.